PEMBERIAN MAKANAN TAMBAHAN SEBAGAI UPAYA PENANGANAN STUNTING PADA BALITA DI INDONESIA - Waroh, Yuni Khoirul (Program Studi S1 Kebidanan - Fakultas Sains dan Kesehatan Universitas PGRI Adi Buana Surabaya, 2019)
Stunting (dwarf) is a condition where toddlers have a length or height that is less than age. This condition is measured by length or height which is more than minus two median standard deviations of the child growth standard of the WHO. Stunting toddlers include chronic nutrition problems caused by many factors such as socio-economic conditions, maternal nutrition during pregnancy, pain in infants, and lack of nutritional intake in infants. Stunting toddlers in the future will experience difficulties in achieving optimal physical and cognitive development. The results of the Basic Health Research (Riskesdas) in 2007 showed that the prevalence of short toddlers in Indonesia was 36.8%. In 2010, there was a slight decrease to 35.6%. However, the prevalence of short toddlers again increased in 2013, which was 37.2%. The prevalence of children under five in Riskesdas in 2018 decreased slightly to 30.8%. Based on the Minister of Health Regulation No. 39 of 2016 concerning the Guidelines for Implementing a Healthy Indonesia Program with a Family Approach, efforts made to reduce the prevalence of stunting in children under five are by organizing a supplementary feeding program (PMT). Which is where the Supplemental Feeding will reduce the incidence of stunting in infants.